Right to respect for private and family life and right to non-discrimination of trans people in the Council of Europe legal system - Vallers, Kristofers (Riga Graduate School of Law, 2022)
Transsexuals are one of the LGBTQIA+ community members whose rights have occasionally been overlooked. In some nations, the rights of transgender individuals are included in the legislative process by creating distinct papers outlining those rights and the steps that must be taken by a trans person to feel like a contributing member of society. The question of the Thesis is in what way legal system of the Council of Europe and its member states protects trans people rights? The objectives of the thesis are to understand what LGBTQIA+ are and trans people definitions in different countries legislations and trans people rights in legal documents and international documents, analyse European Convention on Human Rights and compare with Latvia’s and Germany’s legislations and case studies. The result of the Thesis is that Latvia’s must improve legislations towards protecting trans people rights and Germany must improve existing law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; LGBTQIA+ rights; European Convention on Human Rights; discrimination